The effect of metabolic health and obesity phenotypes on risk of hypertension: A nationwide population-based study using 5 representative definitions of metabolic health. Issue 38 (September 2018) - Tian, Simiao; Xu, Yang; Dong, Huimin
Abstract : Abstract: Although obesity is clearly identified as a risk factor for hypertension, the association between its different metabolic phenotypes and hypertension remains unclear. We aimed to investigate this association and compare the degree of association between metabolic health and obesity phenotypes defined by 5 representative criteria and hypertension risk. This study used data from the China Health and Nutrition Survey 2009 wave, and the final analysis included 7632 subjects aged 18 to 85 years with available fasting blood samples and anthropometric measurements. Body mass index was used to define nonobese and obese status in subjects (cut-off value, 25 kg/m 2 ), and metabolic health state was respectively defined by 5 published criteria: the Adult Treatment Panel (ATP)-III, the Wildman, the Karelis, the homeostasis model assessment (HOMA), and the fasting blood glucose × triglyceride (TyG) criteria. Subjects were categorized into 4 phenotypes according to their metabolic health and obesity status: metabolically healthy nonobese (MHNO), metabolically unhealthy nonobese (MUNO), metabolically healthy obese (MHO), and metabolically unhealthy obese (MUO). A total of 2171 subjects (28.4% of the study population) had hypertension, and hypertension prevalence was significantly increased as weight increased for both metabolically healthy and metabolically unhealthy subjects. Within the MHO phenotypes, the prevalence ranged from 22.7% to 38.6% according to the Wildman and HOMA criteria, respectively. Compared to the MHNO phenotype, the MHO phenotype had an increased risk of hypertension, and the adjusted odds ratios for hypertension in MHO subjects were 1.94 (95% confidence interval 1.60–2.35) using the ATP-III criteria, 1.98 (1.61–2.43) using the Wildman criteria, 2.37 (1.88–2.99) using the Karelis criteria, 2.26 (1.96–2.61) using the HOMA criteria, and 2.54 (2.14–3.00) using the TyG criteria, respectively. A similar significant pattern was found in the MUO and MUNO phenotypes for risk of hypertension. Furthermore, the MUO phenotype consistently revealed the strongest degree of association with hypertension, following by the MHO and the MUNO phenotype. Both metabolically unhealthy status and obese status contributed to a higher risk of hypertension in Chinese adults. The MHO phenotype was not a benign condition and had substantial risk of hypertension compared to the MHNO phenotype. Thus, metabolic health status and obesity should be monitored together when managing hypertension risk. Abstract : Supplemental Digital Content is available in the text